2013
DOI: 10.1371/journal.pone.0083232
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Phase I Study of PRS-050 (Angiocal), an Anticalin Targeting and Antagonizing VEGF-A, in Patients with Advanced Solid Tumors

Abstract: BackgroundTo report the nonrandomized first-in-human phase I trial of PRS-050, a novel, rationally engineered Anticalin based on human tear lipocalin that targets and antagonizes vascular endothelial growth factor A (VEGF-A). MethodsPatients with advanced solid tumors received PRS-050 at 0.1 mg/kg to 10 mg/kg by IV in successive dosing cohorts according to the 3+3 escalation scheme. The primary end point was safety. ResultsTwenty-six patients were enrolled; 25 were evaluable. Two patients experienced dose-limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 54 publications
0
31
0
1
Order By: Relevance
“…Tear lipocalin is nominally produced in the lung so exogenous protein would not induce antibody formation. Lack of immunogenicity is a feature of one newly engineered anticalin, which is based on the calyx structure and promiscuous ligand binding of tear lipocalin [66]. In our case release of the drug at the target could be enhanced by a number of local conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Tear lipocalin is nominally produced in the lung so exogenous protein would not induce antibody formation. Lack of immunogenicity is a feature of one newly engineered anticalin, which is based on the calyx structure and promiscuous ligand binding of tear lipocalin [66]. In our case release of the drug at the target could be enhanced by a number of local conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Mechanisms of iron acquisition and retention are enhanced in cancer cells [9], and the expression of genes that regulate iron metabolism are predictive of cancer patient outcome [22]. As a consequence, iron chelation is under active investigation as a potential anti-tumor strategy [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have observed that the synthesis of hepcidin by tumors acts in an autocrine fashion to decrease ferroportin and thus restrict iron efflux out of tumor cells, promoting tumoral iron retention [7,8]. Since iron promotes tumor cell proliferation and metastasis [9], blocking hepcidin synthesis represents a potential strategy for limiting tumor growth, and might represent an additional use for commercially developed hepcidin antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…[122] Another Anticalin developed by Pieris Pharmaceuticals, Inc. was well tolerated in a phase 1 trial. [123] Results are pending from a phase 1 clinical trial of PRS-080 which concluded this year. [124] Pending favorable results, Pieris Pharmaceuticals, Inc. intends to initiate phase 2 trials in patients with chronic kidney disease suffering from functional iron deficiency anemia.…”
Section: Hepcidin Antagonistsmentioning
confidence: 99%